2005
DOI: 10.4103/0028-3886.22611
|View full text |Cite
|
Sign up to set email alerts
|

Artificial cervical disc replacement: Principles, types and techniques

Abstract: Cervical arthroplasty after anterior decompression with insertion of a prosthetic total disc replacement has been suggested as an alternate to anterior cervical fusion. Currently there are four cervical arthroplasty devices available on the market whose results in clinical use have been reported. Each device varies in terms of materials, range of motion, insertion technique and constraint. It is not known which device is ideal. Early studies suggest that in the short term, the complication rate and efficacy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 30 publications
0
34
0
1
Order By: Relevance
“…They should also restore the physiologic range of motion, be able to restore disc height, and transmit axial loading forces from the superior vertebral body to the one inferior [68]. Chang et al [69] found that following TDR, the facet loads increased at the index level in all the bending modes, with maximum in extension.…”
Section: Facet Joint Loadingmentioning
confidence: 99%
“…They should also restore the physiologic range of motion, be able to restore disc height, and transmit axial loading forces from the superior vertebral body to the one inferior [68]. Chang et al [69] found that following TDR, the facet loads increased at the index level in all the bending modes, with maximum in extension.…”
Section: Facet Joint Loadingmentioning
confidence: 99%
“…Anterior approach includes traditional ACDF, artificial disc replacement, and anterior transcorporeal disc resection [15,16]. Postoperative dysphagia and risks of violation of the esophagus or recurrent laryngeal nerve during operation are well-known complications of anterior cervical approaches, although each method can produce good clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…In order to protect the facet joints from abnormal stresses, cervical arthroplasty devices should have an axis of rotation that mimics the kinematics of the normal spine. They should also restore physiologic range of motion, be able to restore disc height, and transmit axial loading forces from the superior vertebral body to the one inferior [14]. …”
Section: Rationale Of Cervical Arthroplastymentioning
confidence: 99%
“…Cobalt–chrome is commonly considered as biocompatible with advantageous mechanical properties. However, this does significantly interfere with potential future imaging studies such as CT and MRI [14, 30]. Stainless steel is similarly biocompatible and less expensive to fabricate but has a high modulus of elasticity which may be related to subsidence.…”
Section: Design Considerationsmentioning
confidence: 99%